Pengaruh Pendekatan Interactive Conceptual Instruction (ICI) Dengan Media Pembelajaran Terhadap Penguasaan Konsep - Astuti, Dewi; Kurnia Sari, Adila Putri; Marthaningrum, Etty (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2023)
Learning by understanding the concept is a student activity to make conceptual changes. This study aims to determine the effect of the Interactive Conceptual Instructions approach with media (video and images) on mastery of concepts. This study uses a quasi-experimental type with experimental methods. The population in this study were all fourth grade students at SD N Laweyan District for the 2019/2020 academic year. The sample in this study amounted to 236 students. The sampling technique in this study used a stratified cluster random sampling technique. The data collection instrument in this study was a concept mastery test. The hypothesis was tested using a 2x2 unequal cell ANOVA with the help of SPSS software version 21. The results of this study prove that the results of the interaction test of the influence of learning media on mastery of concepts show a significance level of 0.000 which is smaller than 0.05; then H0A is rejected. So it can be concluded that there is an influence of the use of learning media on concept mastery.